Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1074/jbc.m114.623611
|View full text |Cite|
|
Sign up to set email alerts
|

WD Repeat-containing Protein 5 (WDR5) Localizes to the Midbody and Regulates Abscission

Abstract: Background: WDR5 is a protein known for its role in the epigenetic control of gene expression. Results: During cytokinesis, WDR5 resides at the midbody in the absence of chromatin and promotes normal abscission. Conclusion: WDR5 is a midbody component and regulates the final steps of cytokinesis. Significance: WDR5 may have additional functions and binding partners outside of the cell nucleus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 82 publications
0
26
0
Order By: Relevance
“…WDR5 localizes to the mitotic spindle and to the midbody in dividing human cells [ 80 , 81 ]. This localization depends on the integrity of the Win site, as mutations in this site of WDR5 prevent its stable association with the midbody [ 80 ].…”
Section: Wdr5 Moonlights Off Chromatinmentioning
confidence: 99%
See 1 more Smart Citation
“…WDR5 localizes to the mitotic spindle and to the midbody in dividing human cells [ 80 , 81 ]. This localization depends on the integrity of the Win site, as mutations in this site of WDR5 prevent its stable association with the midbody [ 80 ].…”
Section: Wdr5 Moonlights Off Chromatinmentioning
confidence: 99%
“…WDR5 localizes to the mitotic spindle and to the midbody in dividing human cells [ 80 , 81 ]. This localization depends on the integrity of the Win site, as mutations in this site of WDR5 prevent its stable association with the midbody [ 80 ]. Every indication is that binding of WDR5 to the midbody and spindle is functionally relevant, as these WDR5 Win site mutants also fail to rescue mitotic defects associated with WDR5 knock-down [ 82 ].…”
Section: Wdr5 Moonlights Off Chromatinmentioning
confidence: 99%
“…In addition to JADE1S, several transcription factors, histone and DNA modifiers with predominantly nuclear localization such as Brd4 and WDR5, have been found to regulate cytokinesis and abscission 44, 45 . Recently, it has been reported that the novel Abscission/NoCut Checkpoint Regulator (ANCHR) protein functions in Aurora-B-dependent abscission checkpoint control in HeLa cells 46 .…”
Section: Cellular and Biochemical Functionmentioning
confidence: 99%
“…Recently, more and more epigenetic regulating proteins, which mainly localize in the nucleus in interphase, have been reported to obtain new localizations and functions during mitosis. Some typical examples are that HDAC3 localizes on the spindles and affects spindle assembly (38); MeCP2 co-localizes with centrosomes and spindles, and its loss disturbs spindle morphology and mitosis (39); and WDR5 shows localization on the midbody during cytokinesis and regulates this process (40). In our study, immunostaining showed that JMJD5 also changed its localization during mitosis.…”
Section: Discussionmentioning
confidence: 72%